Optimizing Job Satisfaction Through Financial Compensation and Occupational Safety and Health (OSH) - Sidiq Abdullah; Sunimah Sunimah (International Journal Labs, 2026)
Within the domain of human resource management, employee job satisfaction constitutes a fundamental element, as it directly enhances organizational effectiveness and sustainability. This study investigates the impact of financial compensations and occupational safety and health (OSH) on job satisfaction. A survey instrument that completed thorough validity and reliability evaluations was used to gather data from 100 participants utilizing a quantitative research methodology. With a coefficient of 0.459, a t-value of 6.520, and a significance level of 0.000, the use of multiple linear regression analysis demonstrated that financial compensation considerably and favorably effects job satisfaction. Similarly, occupational safety and health exhibited a significant positive impact, marked by a coefficient of 0.268, a t-value of 4.317, and a significance level of 0.000. The joint significance test yielded an F-statistic of 52.596 (significance level 0.000), validating that the independent variables collectively affect employee satisfaction. Consequently, these outcomes underscore the criticality of integrating competitive financial packages with robust safety protocols to maximize overall job satisfaction.